La Virginidad cristiana en Clemente de Alejandría - Llopis, Ángel Gerónimo (Veritas, 2019)
The present study investigates the Christian option for virginity in the thought of Clement of Alexandria. In our author there is no organized doctrine about Christian virginity, however, it is surprising that if these isolated comments are studied together, we can discover clearly and accurately the thought of the master of Alexandria about virginity within Christianity. In this study, the textual citations of the works of Clement of Alexandria will serve as reference and will guide us in the development of his vision of Christian virginity.